The Effect of Entrepreneurial Motivation, Risk-Taking Propensity, and Creativity on MSME Sustainability with Business Innovation as an Intervening Variable and Family Support as a Moderating Variable - Wanda Desta Arlina; Pahrudin; Muh. Fahrurrozi (LP2M IAIN Palopo, 2026)
This study aims to analyze the influence of entrepreneurial motivation, risk-taking, and creativity on the sustainability of MSMEs, with business innovation as an intervening variable and family support as a moderating variable. The method used was a quantitative approach with an explanatory research design. Data were collected through questionnaires from MSMEs in West Nusa Tenggara (NTB) using purposive sampling and analyzed using SEM-PLS. The results show that entrepreneurial motivation, risk-taking, and creativity significantly influence business innovation. Business innovation significantly influences MSME sustainability and mediates this relationship. Family support has a direct effect on MSME sustainability but does not act as a moderating variable.The implications of this study emphasize the importance of business innovation as a key to improving MSME sustainability.